PENGADAAN TANAH DAN PROBLEM PERMUKIMAN KEMBALI: SKEMA PEMBERDAYAAN UNTUK PERLINDUNGAN MASYARAKAT TERDAMPAK - Pujiriyani, Dwi Wulan (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
One of the trigger for conflict in the case of land acquisition is the idea of resettlement as a form of compensation. There are many cases of resettlement that end up with rejection by the society. Resettlement in the case of land acquisition most likely to be responded as a negative action which related to eviction or expulsion. Furthermore, this paper will reveal the problem of resettlement in the implementation of land acquisition in Indonesia. This can be related to the model of community empowerment which possibly could become a constructive solution to bridge the need of development and the need of persons affected by development project to protect their rights.This study was conducted due to searching and studying secondary source that discussed about development-induced resettlement. The result shows that resettlement could not only be defined as a physical displacement. Resettlement has to be planned and implemented appropriately so that its effect was not exacerbating the affected communities. Keywords: Land acquisition, compensation, resettlement, empowering